Balkanski špijun - Nikolić, Božidar; Kovačević, Dušan (Yugoslavia : Union Film, 1981)
This tragicomedy is set in the midst of communist era in Yugoslavia. Ilija Čvorović, a former Informbureau member who spent years in prison because of his activities, is called in by the police to answer routine questions about his new subtenant. After working in Paris as a tailor for twenty years, Petar Jakovljević recently returned to his homeland where he wants to open a tailor’s shop. Though the inspector does not find anything suspicious in Ilija’s report, Čvorović is soon convinced that his subtenant represents a threat to national security. When the police ignore his warnings, he begins his own hilarious surveillance operation against the innocent man. His paranoia grows every day and he even manages to convince his wife and twin brother that the subtenant is an agent of imperialist powers. Assured that he has uncovered a major conspiracy, Ilija invites his brother to help him “dispose of the enemy.” In the final confrontation, he suffers a heart attack and Jakovljević manages to escape after first calling the ambulance. Ilija’s last thoughts are still focused solely on stopping the “enemy.”
Duration: 01:35:00
Keywords: Fiction films